2017
DOI: 10.18632/aging.101219
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles and function analysis of microRNAs in postovulatory aging mouse oocytes

Abstract: In this study, microRNA (miRNA) profiles in postovulatory aging mouse oocytes were analyzed by microarray screening and RT-qPCR. Hierarchical cluster analysis on the microarray data and KEGG pathway enrichment analysis on the mRNAs targeted by differentially expressed (DE) miRNAs between two adjacent egg-ages suggest that while only a mild alteration in miRNA expression occurred from 13 to 18 h, a great change took place from 18 to 24 h post hCG injection. Theoretical exploration on functions of the predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Depleted ER Ca 2+ stores explain, on the other hand, the lower amplitude of Ca 2+ transients in postovulatory aged oocytes, which accords with the previous reports 4,53,54 . It has been suggested that the decreased amount of Ca 2+ stored in the ER of ageing oocytes may be caused by a Ca 2+ leak resulting from expression of a truncated caspase 3-cleaved form of IP3R1 27,55,56 , likely triggered by increased expression of miR-98 57 . The low amplitude of Ca 2+ oscillations can be also related to the deregulation of other posttranslational modifications of IP3R1.…”
Section: Resultsmentioning
confidence: 99%
“…Depleted ER Ca 2+ stores explain, on the other hand, the lower amplitude of Ca 2+ transients in postovulatory aged oocytes, which accords with the previous reports 4,53,54 . It has been suggested that the decreased amount of Ca 2+ stored in the ER of ageing oocytes may be caused by a Ca 2+ leak resulting from expression of a truncated caspase 3-cleaved form of IP3R1 27,55,56 , likely triggered by increased expression of miR-98 57 . The low amplitude of Ca 2+ oscillations can be also related to the deregulation of other posttranslational modifications of IP3R1.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, these effects are associated with infertility. miRNAs identified play various roles in the ovary, oocyte, and early embryo, including hormone production, cell cycle progression, cell fate determination, folliculogenesis, oocyte maturation, fertilization, and embryo development 48 , 49 , 50 .…”
Section: Micrornas In Reproductionmentioning
confidence: 99%
“…Several studies reported the presence of functional miRNAs in murine, bovine, or porcine oocytes (Chen et al , 2012; Sinha et al , 2017; Wang et al , 2017; Gad et al , 2020). In these studies, experimental support for significant endogenous miRNA activity in oocytes was inferred from correlative effects of miRNA overexpression or use of antisense inhibitory oligonucleotides (“antagomirs”) (Krutzfeldt et al , 2005).…”
Section: Resultsmentioning
confidence: 99%
“…That would correspond to more than a billion microinjected oligonucleotides, while an oocyte contains tens of millions of mRNA molecules (Fan et al , 2015). Similarly, miR‐98 function in mouse oocytes was studied using microinjection of 10 pl of 50 μM miRNA or 100 μM inhibitors (Wang et al , 2017). Since cytoplasmic volume of a mouse oocyte is ~260 pl, such experimental design would result in micromolar concentrations of microinjected oligonucleotides in the cytoplasm.…”
Section: Resultsmentioning
confidence: 99%